Two parallel do not intersect.

Now, the lines we have are:

y= 3(x-2) and 2y = 6x -9

2y = 6x -9

=> y = ( 6x - 9)/2

=> y = 3x - 9/2

Now we see that y= 3(x-2) => y - 3x = -6 and y =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Two parallel do not intersect.

Now, the lines we have are:

y= 3(x-2) and 2y = 6x -9

2y = 6x -9

=> y = ( 6x - 9)/2

=> y = 3x - 9/2

Now we see that y= 3(x-2) => y - 3x = -6 and y = 3x - 9/2 => y - 3x = -9/2 are two non - intersecting lines.

**Therefore they are parallel.**

Given the lines:

y= 3(x-2)

2y = 6x -9

We need to determine if the lines are parallel.

First we will rewrite he equations of the lines into the slope form.

If the slopes are equal, then the lines are parallel.

==> y= 3(x-2)

==> y= 3x -6 ==> the slope m1 = 3

2y = 6x -9

Divide by 2:

==> y= 3x - 4.5 ==> the slope m2= 3

Then, we notice that m1= m2.

**Then, the lines are parallel.**